A Comprehensive Review of Specific Yield in Land Surface and Groundwater Studies. (16th February 2021) - Lv, Meizhao; Xu, Zhongfeng; Yang, Zong‐Liang; Lu, Hui; Lv, Meixia
Abstract: Specific yield is a key parameter for estimating water table depth in land surface models, which can strongly modulate the interaction between soil moisture and groundwater and further affect the water budget between the land surface and the atmosphere. The error in water table simulation comes mainly from the uncertainty in determining the specific yield. The determination of specific yield in land surface models is simplified, and a uniform empirical constant value of specific yield is generally used in global simulations, especially for deep aquifers, for its convenience. However, a uniform fixed value is insufficient for worldwide aquifers with diverse environments. Before estimating specific yields for global aquifers in Earth system simulations, a comprehensive understanding of the specific yield and comparison of current determination methods are required. This study provides a comprehensive review of the literature focusing on different concepts of the specific yield, complex variabilities, and various determination methods. Specifically, we detail the distinction and interconversion of different subconcepts that are used to reflect the influence of different factors on the specific yield and are likely to confuse scholars; present the representative comparisons of previous estimated specific yields using different methods, and summarize the applicabilities and limitations of these methods, indicating directions for their future improvement. Key Points: Specific yield is a key parameter for estimating water table depth A uniform empirical constant value of specific yield used in global simulations is unsuitable This paper provides a comprehensive review to guide specific yield estimations Plain Language Summary: The specific yield parameter, which is the space available for the gain or loss of groundwater associated with the rise or fall of a water table, is used to calculate water table depth. The key error in water table simulation mainly comes from the uncertainty in determining the specific yield. The determination of specific yield in land surface models is simplified. A uniform empirical constant value of specific yield is used for its convenience in global simulations, especially for deep aquifers. A uniform value is insufficient for worldwide aquifers with diverse environments. Before estimating specific yields for both a global simulation and different local aquifers, a comprehensive understanding of the specific yield and comparison of current determination methods are required. In this review study, we distinguish different subconcepts of specific yield which are likely to confuse scholars; present the representative comparisons of previous estimated specific yields using different determination methods, and summarize the applicabilities and limitations of these methods.